Use of linked hospital-based morbidity surveillance to explain trends in mortality in Kilifi Health and Demographic Surveillance System - Deribew, A; Moïsi, J; Deribew, A; Nokes, D; Bauni, E; Oteinde, M; Nyundo, C; Mwango, L; Ojal, J; Marsh, K; Snow, R; Williams, T; et al. (2015)
Background The Kilifi Health and Demographic Surveillance System (KHDSS) is the largest population under continuous mortality surveillance in tropical Africa. Admissions to Kilifi County Hospital, the only inpatient facility in KHDSS, are linked to the KHDSS population register creating passive morbidity surveillance. We analysed the cause-specific incidence of hospital admissions and prevalence to interpret mortality trends in the KHDSS.